(untitled) (Praxis Educativa, 2022)
This reflection article has the purpose to analyze the possibilities of the desire in the school. Thus, a pedagogy of desire is presented, articulated to three educational and curricular principles of the 21st century, as a call to the endurance, to the solidarity and to the responsibility to overcome the hopelessness of the current crises. The text is structured in three parts. In the first, an approach to desire is made –bound to the Eros and to the literature- as a way to confront with financial capitalism. In the second, it deepens in three dimensions of the desiring spirit, under an idea of integration and simultaneity. Finally, the possibilities of the desire in the school educational experience are pointed out. From the above, it is concluded that if the school education aspires to transcend and face the current crises, it must take the desire -and therefore the endurance- as a founding principle of its interactions, where the desire for the other, for oneself and for the knowing is an opportunity that moves to action in search of a preferable common life.